Estimation of friction factor at workpiece–die interface in combined forward and backward hollow extrusion of brass at micro scale. (May 2014) - Chang, C. C.; Hsu, C. H.; Lai, J. C.
<x content-type="archive" xml:space="preserve">Abstract</x> Friction at the workpiece–die interface significantly affects material flow behaviours in micro metal-forming processes. The purpose of this study was to estimate the friction factor at the workpiece–die interface in the combined forward and backward hollow extrusion of brass at micro scale. The effects of grain size and lubricating conditions on the friction were investigated. The brass (JIS C2700) tubes with 1·1 mm outer diameter and 0·5 mm inner diameter were annealed at 400, 500 and 600°C, and resulted in various microstructures with grain sizes of 20, 34 and 80 μm, respectively. The tubes were fabricated as 0·6 mm length specimens for the experiments of the hollow extrusion under dry, full and punch lubricated conditions. By comparing the ratios of the cup height to the rod length of the extruded specimens with the calibration curves established by finite element simulations, it is possible to estimate the friction factors in the processes. The results show that dry conditions lead to stronger friction effects and thus larger friction factors. The friction factor increased with grain size and stroke for all conditions. The estimated friction factors were in a range from 0·1 to 0·35.